2015
DOI: 10.1080/14786419.2015.1016939
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolates from lavender (Lavandula angustifolia) – their chemical composition as well as aromatic, antimicrobial and antioxidant properties

Abstract: It was shown that the method for obtaining hydrolates from lavender (Lavandula angustifolia) influences the content of active compounds and the aromatic, antimicrobial and antioxidant properties of the hydrolates. The content of volatile organic compounds ranged from 9.12 to 97.23 mg/100 mL of hydrolate. Lavender hydrolate variants showed low antimicrobial activity (from 0% to 0.05%). The radical scavenging activity of DPPH was from 3.6 ± 0.5% to 3.8 ± 0.6% and oxygen radical absorbance capacity (ORAC(FL)) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 13 publications
1
31
0
1
Order By: Relevance
“…EO of lavender (Lavandula angustifolia) has long been used in folk medicine, cosmetics and aromatherapy [43,44]. Several studies confirmed that LO is useful in the treatment of skin ulcers [45], lesions [46] and burns, thanks to its analgesic and anti-microbial properties [23]. Antibacterial effects of LO were proved against MRSA (methicillin-resistant Staphylococcus aureus) [47], Propionibacterium acnes [48] and Candida albicans [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EO of lavender (Lavandula angustifolia) has long been used in folk medicine, cosmetics and aromatherapy [43,44]. Several studies confirmed that LO is useful in the treatment of skin ulcers [45], lesions [46] and burns, thanks to its analgesic and anti-microbial properties [23]. Antibacterial effects of LO were proved against MRSA (methicillin-resistant Staphylococcus aureus) [47], Propionibacterium acnes [48] and Candida albicans [49].…”
Section: Discussionmentioning
confidence: 99%
“…Majority of results concerning the effects of lavender in different model systems was obtained with lavender oil or with some of the major components of L. angustifolia. Lavender essential oil, volatile aromatic oily liquid isolated from Lavandula plants, possesses many therapeutic properties including antioxidant, anti-inflammatory [22], antimicrobial [23], antiplatelet and antithrombotic [24], antimutagenic [25] and chemopreventive [26] activities. Lavender essential oil is commonly used in aromatherapy and massage.…”
mentioning
confidence: 99%
“…In addition, L. latifolia has demonstrated significant antioxidant properties, attributing this activity to the rosmarinic acid and apigenin components present in the hydrosol [97]. However, a recent study has demonstrated that the antioxidant activity of L. angustifolia hydrolates is significantly lower than that of the essential oil, due to the low content of volatile organic compounds in the hydrolate [98]. Still, it is clear that lavender hydrosols generated by the distillation industry could, in fact, be valorized and utilized as a natural source of antioxidants.…”
Section: Antioxidant Properties Of Lavandula Extractsmentioning
confidence: 99%
“…Hydrolates are complex mixtures containing traces of related EOs, and many water-soluble components. They are easy and inexpensive to produce and less toxic than their corresponding EOs [13,14]. Hydrolates are used in the aqueous phase in the manufacture of lotions, and creams and soaps, or independently as tonics and air fresheners, as well as in the food industries.…”
Section: Introductionmentioning
confidence: 99%